2017
DOI: 10.3389/fpsyg.2017.00839
|View full text |Cite
|
Sign up to set email alerts
|

Parenting Stress, Mental Health, Dyadic Adjustment: A Structural Equation Model

Abstract: Objective: In the 1st year of the post-partum period, parenting stress, mental health, and dyadic adjustment are important for the wellbeing of both parents and the child. However, there are few studies that analyze the relationship among these three dimensions. The aim of this study is to investigate the relationships between parenting stress, mental health (depressive and anxiety symptoms), and dyadic adjustment among first-time parents.Method: We studied 268 parents (134 couples) of healthy babies. At 12 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
78
2
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 104 publications
(101 citation statements)
references
References 76 publications
14
78
2
7
Order By: Relevance
“…Rolle et al . compared the scores of the PSI‐SF consisting of 36 items for 134 pairs of mothers and fathers with children aged 1 year (boys, 61%; girls, 39%), and reported that PD was higher in mothers . Van der Veen‐Mulders et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rolle et al . compared the scores of the PSI‐SF consisting of 36 items for 134 pairs of mothers and fathers with children aged 1 year (boys, 61%; girls, 39%), and reported that PD was higher in mothers . Van der Veen‐Mulders et al .…”
Section: Discussionmentioning
confidence: 99%
“…Rolle et al compared the scores of the PSI-SF consisting of 36 items for 134 pairs of mothers and fathers with children aged 1 year (boys, 61%; girls, 39%), and reported that PD was higher in mothers. 18 Van der Veen-Mulders et al compared the scores of PSI-SF consisting of 25 items for parents of 72 preschool children with ADHD (average age, 54.8 AE 11.0 months; boys, 81%; girls, 19%) and 80 preschool children with no ADHD (average age, 47.3 AE 12.7 months; boys, 53%; girls, 47%), and reported that the total PSI score was higher in mothers of children with ADHD than fathers, while there was no significant difference between the mothers and fathers of children with no ADHD. 3 Davis and Carter compared the scores of PSI-SF consisting of 36 items for 54 couples of mothers and fathers of children with ASD (average age, 26.9 AE 4.2 months; boys, 74%; girls, 26%) in the USA, and reported that DC and PD were higher in mothers.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, comparing mother-child interactions during feeding and play provides a unique insight in the pervasiveness of parent-child relational difficulties and therefore informs intervention. From this perspective, our findings may have valuable clinical implications, especially for intervention strategies focused on the quality of the parent-child relationship to support the affective communication within the dyad and to prevent relational disturbances in early childhood (Chatoor, 2009;Cohen, Lojkasek, Muir, Muir, & Parker, 2002;Rollè et al, 2017;Rosenblum, 2004;Sameroff, McDonough, & Rosenblum, 2004;Vismara et al, 2016).…”
Section: Conclusion and Clinical Implicationsmentioning
confidence: 93%
“…Research has shown that decreased marital quality is associated with a higher degree of parenting stress, and that parenting stress influences parenting behavior and promotes dysfunctional parenting (Lavee, Sharlin, & Katz, ). More recent research has suggested that mental health in terms of depression and anxiety mediates between parenting stress and the dyadic adjustment of the parents postpartum at 12 months (Rollè, et al., ). Higher scores on the spousal subdomain of the parenting stress domain are indicative of parents who lack emotional and active support of the partner in child management (Webster‐Stratton, ).…”
Section: The Spousal Relationship and Paternal Stressmentioning
confidence: 99%
“…The PSI has been used to explore parental stress in many different parent–child contexts, such as in the case of twin birth (Prino et al., ), hyperactive and physically abused children (Mash & Johnson, ), and autism spectrum disorders (Davis & Carter, ), and to study the relationship between parenting stress, mental health, and dyadic adjustment among first‐time parents of 12‐month‐old children (Rollè, et al., ). However, to our knowledge, there has been little research on fathers’ stress using the PSI during pregnancy and in the child's first year of life.…”
mentioning
confidence: 99%